Anterograde trafficking of Toll‐like receptors requires the cargo sorting adaptors TMED ‐2 and 7 - Holm, Julia E. J.; Soares, Sandro G.; Symmons, Martyn F.; Huddin, Afiqah Saleh; Moncrieffe, Martin C.; Gay, Nicholas J. (Traffic (Copenhagen, Denmark), 2023)
Toll‐Like Receptors (TLRs) play a pivotal role in immunity by recognising conserved structural features of pathogens and initiating the innate immune response. TLR signalling is subject to complex regulation that remains poorly understood. Here we show that two small type I transmembrane receptors, TMED2 and 7, that function as cargo sorting adaptors in the early secretory pathway are required for transport of TLRs from the ER to Golgi. Protein interaction studies reveal that TMED7 interacts with TLR2, TLR4 and TLR5 but not with TLR3 and TLR9. On the other hand, TMED2 interacts with TLR2, TLR4 and TLR3. Dominant negative forms of TMED7 suppress the export of cell surface TLRs from the ER to the Golgi. By contrast TMED2 is required for the ER‐export of both plasma membrane and endosomal TLRs. Together, these findings suggest that association of TMED2 and TMED7 with TLRs facilitates anterograde transport from the ER to the Golgi.